2020
DOI: 10.3201/eid2608.191724
|View full text |Cite
|
Sign up to set email alerts
|

mcr-Positive Escherichia coli ST131-H22 from Poultry in Brazil

Abstract: Her primary research interests are severe respiratory viral infections in children and the elderly, and molecular epidemiology studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Whereas E. coli ST131-H30 is the most prevalent sublineage causing extraintestinal infections in humans (Dahbi et al, 2014;Matsumura et al, 2015;Mamani et al, 2019), ST131-H22 predominates in animals, contaminating associated meat products, and can be transmitted zoonotically (Liu et al, 2018;Roer et al, 2019;Saidenberg et al, 2020). Findings from our phylogenetic analysis showed that avian, swine, and human ST131-H22 strains were closely related, supporting results from previous studies (Liu et al, 2018;Reid et al, 2019;Roer et al, 2019;Saidenberg et al, 2020), and also included our environmental strain in the same cluster as those strains (Figure 2), highlighting their transmission at the human-animalenvironment interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas E. coli ST131-H30 is the most prevalent sublineage causing extraintestinal infections in humans (Dahbi et al, 2014;Matsumura et al, 2015;Mamani et al, 2019), ST131-H22 predominates in animals, contaminating associated meat products, and can be transmitted zoonotically (Liu et al, 2018;Roer et al, 2019;Saidenberg et al, 2020). Findings from our phylogenetic analysis showed that avian, swine, and human ST131-H22 strains were closely related, supporting results from previous studies (Liu et al, 2018;Reid et al, 2019;Roer et al, 2019;Saidenberg et al, 2020), and also included our environmental strain in the same cluster as those strains (Figure 2), highlighting their transmission at the human-animalenvironment interface.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on the ST131-H30 sublineage, which is one of the leading causes of extraintestinal infections in humans, including C2 subclade associated with the bla CTX−M−15 gene (Dahbi et al, 2014;Matsumura et al, 2015;Mamani et al, 2019). In contrast, the most prevalent animal ST131 strains belong to the ST131-H22 sublineage and can be transmitted zoonotically, presenting a public health challenge (Liu et al, 2018;Roer et al, 2019;Saidenberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many antibiotics belonging to different classes, such as tetracyclines (tetracycline, oxytetracycline, chlortetracycline), sulfonamides (sulfadimethoxine, trimethoprim, sulfadiazine, sulfamethazine, sulfaquinoxaline, ormethoprim), aminoglycosides (apramycin, gentamicin, neomycin, spectinomycin), penicillins (amoxicillin, ampicillin), cephalosporins (ceftiofur), quinolones (danofloxacin, sarafloxacin, enrofloxacin), polymyxins (colistin), chloramphenicols (florfenicol), macrolides (erythromycin), and lincosamides (lincomycin) have been used in poultry industry worldwide for the control of APEC infections [ 23 ]. However, APEC resistance to multiple antibiotics has been reported [ 32 , 34 , 35 , 51 , 53 , 54 , 70 , 71 , 72 , 73 , 107 , 108 , 108 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ], which limits the use of these antibiotics and suggests a challenge ahead in using these antibiotics. Table 2 provides a summary of antibiotic resistance and resistance genes (mechanisms) reported worldwid...…”
Section: Control Strategiesmentioning
confidence: 99%
“…Investigations of the ExPEC within poultry were mainly focused on the avian pathogenic Escherichia coli (APEC), a subset of ExPEC, from poultry with colibacillosis [ 15 , 16 ] and APEC mainly caused respiratory and systemic disease in poultry; however, the molecular definition criteria of APEC in those studies was different from that of ExPEC [ 6 , 17 ]. Recently, ExPEC isolates within diseased chickens were also reported [ 18 , 19 ]. Notably, the feces of healthy chickens also carried ExPEC isolates [ 14 , 20 ], and the fecal ExPEC isolates could contaminate chicken carcasses at slaughter, including from rupture of the digestive system during processing, and then transmitted to humans by the food chain or direct human-animal contact [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of antibiotic resistance, one of the ten threats to global health for 2019 as determined by the World Health Organization, among ExPEC isolates has been another big concern. Antibiotic resistance genes, such as extended-spectrum β-lactamases (ESBLs)-encoding genes have been reported in ExPEC isolates [ 22 ] and ExPEC including those from poultry can also acquire different resistance genes [ 18 ], which would inevitably reduce the therapeutic options, increase morbidity and mortality of ExPEC infections, and eventually bring an increased risk to public health [ 23 , 24 ]. Although antibiotics do not select virulent strains such as ExPEC intrinsically [ 25 ], the heavy use of antibiotics in food-producing animals could facilitate the dissemination of ExPEC because such pathogens from environment and diseased animals have been often reported to be multidrug resistant (MDR) [ 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%